Catalytic Enantioselective Arylboration of Alkenylarenes. Issue 3 (21st December 2016) - Logan, Kaitlyn M.; Brown, M. Kevin
Abstract: A method for the catalytic enantioselective arylboration of alkenylarenes is disclosed. The reaction leads to the formation of 1, 1‐diarylalkanes that also incorporate an additional pinacol boronic ester which can be easily transformed to a variety of groups. The products are formed with excellent diastereoselectivities and enantioselectivities. Abstract : Incorporate and transform : The title reaction yields 1, 1‐diarylalkanes and simultaneously incorporates a pinacol boronic ester, which can be easily transformed to a variety of groups. Products are formed with excellent diastereoselectivities and enantioselectivities.